A global modelling approach of natural ventilation with acoustic and daylighting constraints. Issue 3 (1st October 2016) - Cui, Shuqing; Perret-Gentil, Marcel; Gourdon, Emmanuel; Barthelmé, Anne-France; Mankibi, Mohamed El; Wurtz, Etienne; Stabat, Pascal; Marchio, Dominique
ABSTRACT: Natural ventilation helps to cool buildings in summer without energy consumption, but its application may be restricted by acoustic and glare constraints. Here, a modelling approach integrating different physical aspects was developed and connected to TRNSYS. Different control strategies of glazed openings were defined and simulations were performed with an office room and a detached family house. We find the natural ventilation potential is largely reduced due to acoustic and visual comfort constraints. An acoustic shutter, which facilitates more frequent window opening during occupancy by decreasing outdoor noise transmission, was equally studied in detail with the help of this modelling approach. The acoustic shutter improves the acoustic and thermal comforts for intelligent control strategy and is an attractive solution to enhance the natural ventilation potential under a moderate noisy environment.